MENAKAR ULANG TRADISI ABHAKALAN ANAK DI BAWAH UMUR PADA MASYARAKAT SUKU MADURA - Moh Subhan (ASASI: Journal of Islamic Family Law, 2020)
The Madurese tribe is one of the tribes in Indonesia that has a variety of unique cultures and customs. The heterogeneity of the traditions and customs of the Madurese tribe, until now still maintained neatly, although there are also traditions that have begun to fade. Among the traditions that are still maintained and carried out today is abhakalan. Abhakalan is a form of matchmaking in the Madurese tribe, where the child's match is arranged and determined by both parents or close relatives so that children cannot choose their own partner to be their life partner. Abhakalan is done by parents of their children has adults or still child who are still minors, even children who are still in the womb. The attitude of children's obedience to parents among Madurese is still very high. Parents, families, or community have a greater role to answer basic questions related to abhakalan. In this case abhakalan is done as an effort to maintain the integrity of the brotherhood (sa taretanan) and kinship (sa bhela’an) of each of these families, so that their families remain intact and large. In addition, so that the inheritance does not fall into the hands of others. Although it cannot be denied, that the tradition of abhakalan in minors that has occurred from generation to generation can have positive and negative impacts, depending on how the both sides of the family maintain harmonious communication and relationships between families.